Thy Kingdom Come? Visualizing (Post)Colonial Futures in the German Southwest - Krause, Katharina 1984-; Pittl, Sebastian 1984- (2023)
The future of colonial pasts still haunts Christian imagination and theology. This is especially true in the field of eschatology, which is dedicated to Christian ways of conceiving the future. This article examines the manifold entanglements that collude in the fabrication of Christian imaginaries of time, future, and global community within (post)colonial conditions. At the center of the article resides the case study of a lithograph distributed by missionary networks in the second half of the 19th century and passed down over three generations in a German Swabian craftsman’s family. The first part of the article offers a detailed image analysis of the lithograph, paying special attention to its ways of religious and colonial worlding. The second examines the social milieu of the addressees of the lithograph and analyzes its embeddedness in intersectional webs of religious, aesthetic, and social disciplining. It draws attention to the complex, often ambiguous dynamics involved in producing colonial inferiority. Against this background, the third part explores, in the form of a provisional thought experiment, ways of a decolonial revision of the lithograph, which bring the aforementioned ambivalences “into view” and interrupt its temporal hierarchization.
Keywords: Eschatology; Postcolonialism; non-simultaneity; German southwest; Gruorn; Karl Schönherr; pious imaginaries; Aesthetics; Mission